Synthesis and Biological Evaluation of Hapten‐Clicked Analogues of The Antigenic Peptide Melan‐A/MART‐126(27L)‐35. (6th April 2020) - Tarbe, Marion; Miles, John J.; Edwards, Emily S. J.; Miles, Kim M.; Sewell, Andrew K.; Baker, Brian M.; Quideau, Stéphane
Abstract: A click‐chemistry‐based approach was implemented to prepare peptidomimetics designed in silico and made from aromatic azides and a propargylated GIGI‐mimicking platform derived from the altered Melan‐A/MART‐126(27L)‐35 antigenic peptide ELAGIGILTV. The Cu I ‐catalyzed Huisgen cycloaddition was carried out on solid support to generate rapidly a first series of peptidomimetics, which were evaluated for their capacity to dock at the interface between the major histocompatibility complex class‐I (MHC‐I) human leucocyte antigen (HLA)‐A2 and T‐cell receptors (TCRs). Despite being a weak HLA‐A2 ligand, one of these 11 first synthetic compounds bearing a p ‐nitrobenzyl‐triazole side chain was recognized by the receptor proteins of Melan‐A/MART‐1‐specific T‐cells. After modification of the N and C termini of this agonist, which was intended to enhance HLA‐A2 binding, one of the resulting seven additional compounds triggered significant T‐cell responses. Thus, these results highlight the capacity of naturally circulating human TCRs that are specific for the native Melan‐A/MART‐126‐35 peptide to cross‐react with peptidomimetics bearing organic motifs structurally different from the native central amino acids. Abstract : Click to fit : A computer‐aided construction of a short series of mimetics of the tumor‐derived Melan‐A/MART‐126(27L)‐35 antigenic peptide ELAGIGILTV was achieved by clicking aromatic azido haptens onto a propargylated GIGI‐mimicking central platform. Out of only 18 peptidomimetics thus synthesized, one of the most heavily modified constructs, harboring a p ‐nitrobenzyl moiety, elicited significant Melan‐A‐specific T‐cell responses.@univbordeaux @InstUnivF